Racial/Ethnic Disparities in Sleep Health and Potential Interventions Among Women in the United States - Jackson, Chandra L. (J Womens Health (Larchmt), 2020)
While essential for health and wellness, the various dimensions of sleep health are generally not equitably distributed across the population, and reasons for racial/ethnic sleep disparities are not fully understood. In this review, we describe racial/ethnic sleep disparities and subsequent implications for health from prior and recently conducted epidemiological and clinical studies as well as the potential sleep interventions presented at the 2018 Research Conference on Sleep and the Health of Women at the National Institutes of Health. Given the clear connection between sleep and poor health outcomes such as cardiovascular disease, we concluded that future studies are needed to focus on sleep health in general, sleep disorders such as insomnia and obstructive sleep apnea in particular, and disparities in both sleep health and sleep disorders among women using an intersectional framework. Future research should also integrate sleep into interventional research focused on women's health as these results could address health disparities by informing, for example, future mobile health (mHealth) interventions prioritizing women beyond the clinical setting.